STUDENTS AND LEFT. REFLECTIONS ON THE PERSONAL FUNDS OF THE UNIVERSITY REFORM - Bustelo, Natalia; Sik, María Eugenia (Revista de Historia Social y de las Mentalidades, 2020)
The article adresses in the links between history and archival practice promoted by the Centro de Documentación e Investigación de la Cultura de Izquierdas (CeDInCI, Buenos Aires, Argentina). In the first part we reconstruct the theoretical and methodological problems related to a particular type of archives: personal fonds. Then we expose the characteristics of the documents related to the Reforma Universitaria, that is, the student movement that broke out in Córdoba, Argentina, in 1918 and expanded in the following decades throughout the continent. Finally, from the analysis of some documents, we reflect on the historical and heritage value of the personal archives produced by the Argentine animators of the Reformation.